Mumford and Anjum on incompatibilism, powers and determinism - Mackie, Penelope (Oxford University Press, 2014)
Mumford and Anjum (2014) present a new argument for the incompatibility of free will and causal determinism. Although their argument depends on the assumption that free will is, or is the exercise of, a causal power, it does not appeal to any special features of this power. Their new argument does, however, depend upon a general thesis of the incompatibility of causal powers with causal determinism. I argue that Mumford and Anjum have provided no justification for this general thesis. As a consequence, their new argument for the incompatibility of free will and causal determinism is unsuccessful.